Sabbatical leave report: Spring 2014 - Heidkamp, C. Patrick (2014)
The proposed research project focused on analyzing food system resilience in a small town in eastern Iceland from the perspective of environmental economic geography. In addition to the stated project Heidkamp initiated "a new research project focused on the uniqueness of Nordic Environments, Nordic Spaces and Nordic Places." The sabbatical study yielded panelist and lecturer invitations and conference papers and presentations.
Keywords: dept.egm; faculty_collection; sabbatical_report

A transitions perspective on coastal sustainability - Morrissey, John; Heidkamp, C. Patrick (Towards coastal resilience and sustainability, 2018)
This chapter presents a review of the multi-scalar complexities of coastal sustainability challenges. It focuses on three discrete vignettes of innovation, which range from a novel and emerging innovation, a maturing innovation and an innovation which has become mainstream and part of the prevailing socio-technical regime. The first vignette focuses on 3D ocean farming off the coast of Connecticut in Long Island Sound, USA, as an example of an emerging niche-level innovation. The second vignette discusses the development of offshore wind energy capacity in Liverpool Bay, UK as an example of a socio-technical innovation that is more mature. The final vignette discusses containerisation as an example of a fully matured socio-technological change. The chapter argues that a spatial perspective on transition is critical to adequately account for uneven development processes and to recognise the heterogeneity of different places in terms of potential for low-carbon transition. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Barium alloys; Coastal sustainability; Development process; Liverpool bays; Low-carbon transitions; Off-shore wind energy; Offshore oil well production; Socio-technical regimes; Sociotechnical; Sustainable development; Technological change; Wind power; dept.egm

Tax lien sales as local neoliberal governance strategy: The case of Waterbury, Connecticut - Botein, Hilary; Heidkamp, C Patrick (Local Economy, 2013)
This article examines bulk sales of municipal property tax liens in the formerly industrial city of Waterbury, Connecticut, USA, in the 1990s, in order to explore the limits and contradictions of neoliberal local governance strategies. In the USA, cities and states create property tax liens by reducing delinquent real estate taxes to a judgment that creates a legal claim against the property at issue. We argue that Waterbury's efforts to resolve its fiscal stress by enhancing short-term revenues ultimately further constrained its revenue base, the tax lien sales reflected a spatial selectivity that created barriers to revitalization when neither the city nor tax lien purchasers had incentives to foreclose on distressed properties in struggling neighborhoods, and the tax lien sales' failure to resolve the city's budget crisis set in motion new efforts at tax base enhancement through real estate-led development in the central business district that also were unsuccessful. © The Author(s) 2013 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/002-820-978-161-106 tex.type: [object Object]
Keywords: dept.egm; housing; local government; neighbourhood decline; neoliberalism; real estate taxes; tax liens; urban governance

Geospatial sculpture: Nonverbal communication through the tactilization of geospatial data - Heidkamp, C. Patrick; Slomba, Jeffrey T. (GeoHumanities, 2017)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-225-748-349-137, pop00234
Keywords: 3D visualization; Connecticut; Escultura Geoespacial; GeoSpatial Sculpture; dept.art; dept.egm; geografías no verbales; nonverbal geographies; peer-reviewed; tactilización; tactilization; visualización en 3D; 三维可视化; 地理空间雕塑; 康涅狄格; 触觉化; 非语言的地理

‘Food desertification’: The loss of a major supermarket in New Haven, Connecticut - Russell, Scott E; Heidkamp, C Patrick (Applied Geography, 2011)
In March of 2010, the only full-service supermarket centrally located in New Haven, Connecticut closed, stranding many of the city's residents in a food desert. A food desert is an urban or rural area with significantly limited access to retail sources of healthy and affordable food, due to a combination of socioeconomic disadvantages and physical distance. This article considers the pivotal and causative role of the business model of supermarkets in the creation of new or exacerbation of current urban food deserts, as well as in the impact the loss of one market has on the resilience of the community's food system. Using the events of New Haven as a case study, the form and severity of the food desert in New Haven is analyzed by mapping 1/4 mile, 1/2 mile, and 1 mile road network service areas of the major supermarkets and grocery stores of the area. These are compared against Census block group data of the New Haven population's median household income, poverty level, and access to a personal vehicle. The results show certain parts of the city with low income, high poverty, and low vehicle access to exist in hardship outside the service areas of nearby stores. GIS methodology aids in illustrating the conclusion that the loss of just one supermarket has had significantly detrimental effects on the geographical food access of the city's residents. The ongoing lack of a full-service supermarket in the city not only raises concerns about the value of a new supermarket coming in, but also creates possibilities for seeking alternative food system solutions. (C) 2011 Elsevier Ltd. All rights reserved.
80 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000292537700002, lens.org/010-795-278-274-239 tex.type: [object Object]
Keywords: Connecticut; Food deserts; Food security; GIS; Geographic information systems (GIS); New Haven; Supermarkets; United States; Urban food systems; consumption behavior; dept.egm; food consumption; mapping method; retailing; spatial analysis

The human geographies of coastal sustainability transitions - Axon, Stephen (Towards coastal resilience and sustainability, 2018)
This chapter provides an overview of public engagement, its importance and effective approaches to meaningfully involve the public with coastal sustainability transitions. It presents two case studies, Guernsey, British Channel Islands and Cape Wind, Massachusetts. These illustrate how concepts of identity, marginality and engagement are essential to the development of coastal sustainability transitions. As the case study of Guernsey outlines, coastal sustainability transition-related public engagement should seek to enhance the local distinctiveness of coastal areas and 'fit within the wider narrative of place identity and how individuals feel attached to places that are ascribed with specific meanings'. Furthermore, as the case study of Cape Wind illustrates, coastal sustainability transitions need to connect with local communities in terms of addressing immediate social and economic concerns. Therefore, as a research agenda, the human geographies of coastal sustainability transitions can be of substantial value to the practical application of sustainability. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Case-studies; Coastal sustainability; Economic concerns; Effective approaches; Local community; Massachusetts; Public engagement; Research agenda; Sustainable development; dept.egm

Conclusion: Outlook for coastal transitions - Heidkamp, C. Patrick; Morrissey, John; Morrissey, John (Towards Coastal Resilience and Sustainability, 2018)
Globally, rapid demographic change of coastal urban agglomerations, the speed of urbanisation over time, the overall impact of coastal space occupation as well
Keywords: Climate change; Coastal ecosystems; Coastal zones; Demographic changes; Economics; Ecosystem services; Ecosystems; Energy availability; Flood control; Impervious surface; Long term process; Sea level; Topography; Urban agglomerations; Urban development; Urban growth; dept.egm

Towards Coastal Resilience and Sustainability - Heidkamp, C. Patrick; Morrissey, John; Graves, Scott M. (Routledge, 2019)
"Coastal zones represent a frontline in the battle for sustainability, as coastal communities face unprecedented economic challenges. Coastal ecosystems are subject to overuse, loss of resilience and increased vulnerability. This book aims to interrogate the multi-scalar complexities in creating a more sustainable coastal zone. Sustainability transitions are geographical processes, which happen in situated, particular places. However, much contemporary discussion of transition is either aspatial or based on implicit assumptions about spatial homogeneity. This book addresses these limitations through an examination of socio-technological transitions with an explicitly spatial focus in the context of the coastal zone. The book begins by focusing on theoretical understandings of transition processes specific to the coastal zone and includes detailed empirical case studies. The second half of the book appraises governance initiatives in coastal zones and their efficacy. The authors conclude with an implicit theme of social and environmental justice in coastal sustainability transitions. Research will be of interest to practitioners, academics and decision-makers active in the sphere of coastal sustainability. The multi-disciplinary nature encourages accessibility for individuals working in the fields of Economic Geography, Regional Development, Public Policy and Planning, Environmental Studies, Social Geography and Sociology" – Provided by publisher's website.
Keywords: Coastal zone management; Economic aspects; Economic aspects; Sustainable development; dept.egm; faculty_collection

Forest cover change in the northeastern U.S.: A spatial assessment in the context of an environmental kuznets curve - Bentley, George C; Cromley, Robert G; Hanink, Dean M; Heidkamp, C Patrick (International Journal of Applied Geospatial Research, 2013)
An analysis of the association of forest cover, treated as an environmental good, and income at the county scale in the Northeastern United States was conducted for 2006. Global analysis using a spatial error regression model indicates an environmental Kuznets curve (EKC) type of relationship, with total forest cover, percent forest cover, and forest cover per capita is better associated with per capita income and is better specified as a polynomial rather than in linear terms. Local analysis, using geographically weighted regression, indicates that sub-regional effects are pronounced, and that conformity to an EKC varies spatially and by forest cover measure. The findings should be interpreted strictly within their context of a cross-sectional analysis and within certain statistical limitations, primarily engendered by multicollinearity of the explanatory variables in the regression models. Copyright © 2013, IGI Global.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-145-892-110-132 tex.type: [object Object]
Keywords: Environmental Kuznets Curve; Forest Cover; Geographically Weighted Regression; Northeastern United States; Spatial Error Regression Model; dept.egm

Blue Economy - Germond-Duret, Celine; Garland, Michaela; Heidkamp, C. Patrick; Morrissey, John (International Encyclopedia of Geography, 2016)
Geography has engaged in insightful discussions on how to understand, analyze, criticize, and implement the blue economy. United Nations agencies, Small Island Developing States, and increased academic interest in oceans have played important roles in the global adoption of the blue economy idea, that is, the sustainable exploitation of marine and coastal resources. Geographical research on the blue economy has addressed key themes such as economic and political discourse, relational thinking and assemblage, sustainability and just transitions, and blue economy risks.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118786352.wbieg2166
Keywords: coastal and marine geography; dept.egm; economic development; environmental management; sustainable development

The blue economy: Identifying geographic concepts and sensitivities - Garland, Michaela; Axon, Stephen; Graziano, Marcello; Morrissey, John; Heidkamp, C. Patrick (Geography Compass, 2019)
There is currently no generally accepted definition for the “blue economy,” despite the term becoming common parlance over the past decade. The concept and practice have spawned a rich, and diverse, body of scholarly activity. Yet despite this emerging body of literature, there is ambiguity around what the blue economy is, what it encapsulates, and its practices. Thus far, the existing literature has failed to theorise key geographical concepts such as space, place, scale, and power relations, all of which have the potential to lead to uneven development processes and regional differentiation. Previous research has sought to clarify the ontological separation of land and sea or has conceptualised the blue economy as a complex governmental project that opens up new governable spaces and rationalises particular ways of managing marine and coastal regions. More recently, geographers have called for a critical—and practical—engagement with the blue economy. This paper critically examines the existing literature of the geographies of the blue economy through a structured meta-analysis of published work, specifically its conceptualisations and applications to debates in the field. Results offer the potential to ground a bottom-up definition of the blue economy. In so doing, this paper provides a clearly identifiable rubric of the key geographical concepts that are often overlooked by researchers, policymakers, and practitioners when promoting economic development and technological innovation in coastal and marine environments. © 2019 The Author(s) Geography Compass © 2019 John Wiley & Sons Ltd
48 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/027-155-049-386-765, pop00266 tex.type: [object Object]
Keywords: coastal zone; conceptual framework; dept.egm; economic development; economics; innovation; marine environment; peer-reviewed; power relations; uneven development

Coastal sediment management as a response to intensifying storms and sea level rise: A case study - Tait, James; Orlowski, Ryan; Brewer, Jessica; Miller, Matthew D (Towards coastal resilience and sustainability, 2018)
In a period of rising sea levels and intensifying storms, enhancing coastal resilience and finding sustainable ways of living with the coast have become necessary concerns. Investigations of storm wave damage to coastal structures on the Connecticut shoreline during Hurricane Irene and Superstorm Sandy revealed that the width and height of frontal beaches were the most common denominator in mitigating the damages. One of the major problems, particularly for a state like Connecticut that has a highly developed coastline with systematically eroding beaches, is that the cost of beach nourishment projects is not only high but is increasing rapidly. The cost of beach nourishment at Prospect Beach in the town of West Haven is instructive. However, considering the importance of beaches and the costs of replenishment, rethinking Environmental Protection policies in favour of instituting regional and local sediment management practices may be in order. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Beach nourishment; Beach nourishment projects; Beaches; Coastal sediments; Coastal structures; Common denominators; Sea level; Sea level rise; Sediment management; Shore protection; Storm waves; Storms; Sustainable development; dept.egm